Motivation for Traditional Medicine Micro Enterprises (UMOT) to Upgrade Through Licensing Assistance - Mas'ud, Abdu; Nur, Amran; Rodianawati, Indah; Ibrahim, Abu Rahmat (Agrikan Jurnal Agribisnis Perikanan, 2022)
The increasing use of traditional medicines derived from natural ingredients is increasingly being attracted by the community, so that many traditional medicine UMKM have emerged, especially at the Micro Traditional Medicine (UMOT) level. This service aims to assist UMOT in the City of Ternate in gradually fulfilling CPOTB aspects to obtain BPOM permits. The service method is carried out in several stages, namely the socialization of the application of CPOTB, guidance on the preparation of CPOTB documents, assistance for the application of CPOTB and registration assistance to obtain phase I CPOTB certificates. This service resulted in several advances in UMOT Qonita Production, namely the completion of phase 1 CPOTB documents to carry out online registration.